The Problematika Profesionalisme Keguruan dan HAM dalam Perspektif Kode Etik Guru (Studi Fenomena Kekerasan Secara Fisik Kepada Siswa di Indonesia Tahun 2022) - Fatonah, Siti (Jurnal Kependidikan, 2023)
Abstract To relize the next generation of the nation who are educated and have Pancasila morals, it is necessary to have several supporting roles so that students who after taking education are ready to enter and continue the relay of leadership of this nation. In this case, the main key lies in the role of teachers who can guide and direct their students towards the educational goals of the National Education System, namely Law no. 20 of 2003 article 3 concerning the purpose of education to develop the potential of students to become human beings who believe and fear God Almighty, have noble character, are healthy, knowledgeable, capable, imaginative, independent and incarnate as a democratic nation that is also responsible. However, recently there have been many cases involving teachers and students related to the human rights inherent in every human being since they were born with the professionalism of a teacher. Teachers must maintain the professionalism of a teacher to form a moral person or viewed from the point of view of applicable law in Indonesia and human rights so that students get fair treatment and a sense of security at school. This is the focus of this research on the problems of the teaching profession and human rights in the legal perspective of the teaching profession. The purpose of this study was to determine the relationship between the problem of teacher professionalism and student rights from the perspective of the law of the teaching profession. By using library research methods, namely collecting several data sources in the form of books or journals which are then reviewed to be the object of discussion. The results of the research are that the teachers in carrying out their profession must also apply a code of ethics and respect and respect the human rights of everyone, so that teachers can print the next generation of a nation that is superior and has a Pancasila spirit. . Key word: Acting Part of Parent, Counseling Children Abstrak Untuk mencetak generasi penerus bangsa yang berpendidikan dan bermoral Pancasila memang membutuhkan beberapa peran yang mendukung agar peserta didik yang setelah menempuh pendidikan siap untuk terjun dan meneruskan estafet kepemimpinan bangsa ini. Dalam hal ini, kunci utama terletak pada peran guru yang dapat membimbing dan mengarahkan anak didiknya menuju tujuan pendidikan dari Sisdiknas yaitu pada UU No. 20 Tahun 2003 pasal 3 mengenai tujuan pendidikan untuk mengembangkan potensi peserta didik agar menjadi manusia yang beriman dan bertaqwa kepada Tuhan Yang Maha Esa, berakhlak mulia, sehat, berilmu, terampil, imajinatif, independen dan menjelma sebagai bangsa yang demokratis juga bertanggung jawab. Namun, beberapa peristiwa belakangan ini, banyak terjadi kasus yang menjerat guru dengan siswa yang berkaitan HAM yang melekat pada tiap manusia sejak mereka lahir dengan keprofesionalisme seorang guru. Guru harus tetap mempertahankan keprofesionalnya untuk membentuk manusia yang bermoral ataukah melihat dari pandangan menurut hukum yang berlaku di Indonesia dan HAM bagi siswa untuk mendapat perlakuan adil dan rasa aman di sekolah. Hal inilah yang menjadi focus penelitian ini tentang problematika profesi keguruan dan HAM dalam perspektif hukum profesi guru. Tujuan dari penelitian ini adalah untuk mengetahui keterkaitan masalah profesionalisme guru dengan HAM pada anak didik yang dilihat dalam kacamata kode etik guru Dengan menggunakan metode penelitian library research atau studi kepustakaan yakni mengumpulkan beberapa sumber data berupa buku ataupun jurnal yang dikemudian ditelaah untuk dijadikan obyek pembahasan. Hasil penelitian adalah guru dalam menjalankan profesi nya juga harus menerapkan kode etik dan menjunjung juga menghargai HAM setiap orang, agar guru dapat mencetak generasi penerus bangsa yang unggul dan memiliki jiwa Pancasila. Kata kunci : Profesi Keguruan, HAM, Guru